The importance of international mindedness in promoting intercultural communication within international schools - Trisnawati, Diana; Zakaria, Abd Razak; Kamaruddin, Azni Yati (International Journal of Evaluation and Research in Education (IJERE), 2025)
The globalization has led to an increasing number of international schools worldwide, comprising individuals from diverse cultures. This trend presented numerous multicultural challenges, particularly for those who experience difficulties adapting to multicultural environments. International mindedness (IM) is a crucial aspect of the international baccalaureate (IB) curriculum, playing a significant role in promoting intercultural communication at international schools. This study aimed to explore the significance of IM in fostering intercultural communication, with a specific focus on five teachers in the middle year program (MYP) of two IB schools using a phenomenological approach. Data collection was conducted through semi-structured interviews, and the study employed thematic analysis to address research questions systematically. The findings revealed that participants recognize several elements of IM, including open-mindedness, acceptance of different cultures, empathy, and tolerance. Teachers were identified as vital in developing IM, necessitating them to be respected figures accepted by students and to provide effective teaching strategies. The study highlighted the importance of self-awareness and adaptability skills for teachers in fostering intercultural interactions. A cultural training program can be recommended for developing teachers’ IM, particularly to enhance teachers’ knowledge and perspectives in promoting intercultural communications.